A systematic review and integrative sequential explanatory narrative synthesis: The psychosocial impact of parenting a child with a lysosomal storage disorder. Issue 3 (24th February 2022) - Hassall, Sadie; Smith, Debbie Michelle; Rust, Stewart; Wittkowski, Anja
Abstract: Lysosomal storage disorders are rare multiorgan, degenerative conditions requiring invasive treatment. Rare disorders pose unique challenges; therefore, exploring their impact is crucial for understanding family needs. This novel review aimed to understand the psychosocial outcomes for parents of children with lysosomal storage disorders. Five electronic databases were systematically searched. Thirty‐eight (23 qualitative, 10 qualitative and 5 mixed methods) studies were included, analysed using a sequential explanatory narrative synthesis and appraised for their methodological quality. Quantitative data revealed the multifaceted impact on parents' psychological and social wellbeing. Qualitative data informed the challenges that these parents faced which were expressed within three main themes: (a) Uncertainty and the unknown, (b) All‐encompassing impact and (c) Finding a way forward . The synthesis demonstrated that factors associated with the condition (symptoms, behaviour and severity) had a substantial negative impact on parental outcomes, upheld by concurrent loss (deterioration and poor prognosis) and uncertainty. This substantive integrated review revealed considerable unmet parental psychosocial needs.